Examining communalism in the home math environment to understand its role in predicting children’s mathematics development - McElveen, Tamika L.; Modirrousta, Annahita; Fox, Carlie; Day, John; Salerno, Sophie; Murchland, Abby (Frontiers in Psychology, 2025)
This study investigated the structure of the home math environment (HME) of preschoolers. Examinations include the relation between parental communal beliefs, home math engagement, children’s math skill development, and whether communal beliefs mediated these relations. Parents reported data (N = 652, 49% female, mean age = 4.25; parental demographics: 87.4% White, 9% Latine and Hispanic, 6% African American, 58% 4-year degree or higher, mean income = $70,000–$79,999). The HME structure diverged from prior work. Significant differences were found in home math engagement based on children’s age. Communal beliefs were significantly different based on parental ethnicity and education. While children’s HME and communal beliefs were significantly associated with their math skill development, communal beliefs were not a significant mediator. Overall, this study provided important progress toward understanding the role of these constructs in the development of children’s early math skills.